Problem-oriented charting: A review. (July 2017) - Chowdhry, Shilpa M.; Mishuris, Rebecca G.; Mann, Devin
Highlights: Problem-oriented charting is form of medical documentation that organizes patient data by a diagnosis or problem. Problem-oriented charting provides opportunity for innovation through patient data retrieval tools and problem-oriented templates. Problem-oriented charting offers potential benefit in the clinical setting, but further investigation is still warranted. Before mandating healthcare through the nation to convert to problem-oriented records, additional scrutiny and clinical trials would be beneficial. Abstract: Problem-oriented charting is form of medical documentation that organizes patient data by a diagnosis or problem. In this review, we discuss the history and current use of problem-oriented charting by critically evaluating the literature on the topic. We provide insights with regard to our own institutional use of problem-oriented charting and potential opportunities for research.